Comparing bystander response to a sudden cardiac arrest using a virtual reality CPR training mobile app versus a standard CPR training mobile app - Leary, Marion; McGovern, Shaun K.; Chaudhary, Zainab; Patel, Jaldhi; Abella, Benjamin S.; Blewer, Audrey L. (Resuscitation, 2019)
Using a mobile virtual reality (VR) platform to heighten realism for cardiopulmonary resuscitation (CPR) training has the potential to improve bystander response. We examined whether using a VR mobile application (mApp) for CPR training would improve bystander response compared with a standard mApp CPR training. We randomized lay bystanders to either our intervention arm (VR mApp) or our control arm (mApp). During a post-intervention skills test, we collected bystander response data (call 911, perform CPR, ask for an automated external defibrillator (AED)), along with CPR quality (chest compression (CC) rate and depth). Wilcox rank sum was used to analyze CC rate and CC depth as they were not normally distributed; Pearson’s Chi-square was used to analyze Chain of Survival variables. Between 3/2018 and 9/2018, 105 subjects were enrolled: 52 VR mApp and 53 mApp. Mean age was 46 ± 16 years, 34% were female, 59% were Black, and 17% were currently CPR trained (≤2 years). Bystander response was significantly higher in the VR mApp arm: called 911 (82% vs 58%, p = 0.007) and asked for an AED (57% vs 28%, p = 0.003). However there was no difference in CPR performed (98% vs 98%, p = NS) and the application of the AED (90% vs 93%, p = NS). When comparing the VR mApp to the mApp, mean CC rate was 104 ± 42 cpm vs 112 ± 30 cpm (p = NS), and mean CC depth was 38 ± 15 mm vs 44 ± 13 mm (p = 0.05). The use of the VR mApp significantly increased the likelihood of calling 911 and asking for an AED, however, CC depth was decreased.